Differences in the neural basis and transcriptomic patterns in acute and persistent pain-related anxiety-like behaviors - Fang, Shunchang; Qin, Yuxin; Yang, Shana; Zhang, Hongyang; Zheng, Jieyan; Wen, Songhai; Li, Weimin; Liang, Zirui; Zhang, Xiaomin; Li, Boxing; Huang, Lianyan (Frontiers in Molecular Neuroscience, 2023)
Background: Both acute and persistent pain is associated with anxiety in clinical observations, but whether the underlying neural mechanisms differ is poorly understood. Methods: We used formalin or complete Freund’s adjuvant (CFA) to induce acute or persistent pain. Behavioral performance was assessed by the paw withdrawal threshold (PWT), open field (OF), and elevated plus maze (EPM) tests. C-Fos staining was used to identify the activated brain regions. Chemogenetic inhibition was further performed to examine the necessity of brain regions in behaviors. RNA sequencing (RNA-seq) was used to identify the transcriptomic changes. Results: Both acute and persistent pain could lead to anxiety-like behavior in mice. The c-Fos expression indicates that the bed nucleus of the stria terminalis (BNST) is activated only in acute pain, whereas the medial prefrontal cortex (mPFC) is activated only in persistent pain. Chemogenetic manipulation reveals that the activation of the BNST excitatory neurons is required for acute pain-induced anxiety-like behaviors. In contrast, the activation of the prelimbic mPFC excitatory neurons is essential for persistent pain-induced anxiety-like behaviors. RNA-seq reveals that acute and persistent pain induces differential gene expression changes and protein-protein interaction networks in the BNST and prelimbic mPFC. The genes relevant to neuronal functions might underline the differential activation of the BNST and prelimbic mPFC in different pain models, and be involved in acute and persistent pain-related anxiety-like behaviors. Conclusions: Distinct brain regions and gene expression patterns are involved in acute and persistent pain-related anxiety-like behaviors.